“We Need Each Other!”: Adapting the Tavistock Method for Large Group Therapy for Adults with Severe Mental Illness - Czochara, Bradford (International Journal of Psychosocial Rehabilitation, 2016)
Wilfred Bion (1954) proposed a model of group theory known as a group-as-a-whole approach or the Tavistock method. This approach to group therapy emphasizes the unconscious, group-as-a-whole dynamics versus any individual member’s process. As a means for individuals to deflect discussing their own idiosyncratic trauma history and allowing for a general discussion of trauma, this approach helps members feel safe to risk addressing painful issues in the present moment (Semmelhack, Ende, & Hazell, 2013). We hypothesize that this is the case because the Tavistock method creates, among other things, a deep sense of psychological safety (Hazell, 2005) There are a limited number of research studies examining the applicability, efficacy, and general impact of the Tavistock model on individuals diagnosed with a severe mental illness (Semmelhack, Ende & Hazell, 2013). Additionally, research studies examining the Tavistock model, and its application to group work, focus on small group settings instead of large group settings. This focus on small groups has perhaps resulted from widespread assumptions regarding the tendency for large groups to cause regression and depersonalization in members. This study will highlight on-going research conducted over a six month period of time utilizing a modified Tavistock approach (Semmelhack, Ende & Hazell, 2013) extending the application of the modified Tavistock method to large group work for adults with severe mental illness. It was hypothesized that group members would exhibit increased comfort and cohesiveness in the large group and reduced anxiety regarding engaging in a large group. It was also hypothesized that there would be improvements in other group dynamics such as a stable group size and the understanding of group norms. By this we mean that the group would be well attended by at least a core set of members and that a relatively stable set of growth-promoting norms such as listening and openness to experience would be understood and promulgated by group participants. The authors conducted monthly large group sessions in the style of an adapted Tavistock method (Semmelhack, Ende & Hazell, 2013). Unlike the small groups described in the 2013 study, these large groups included 22-25 members. All groups consisted of members diagnosed with severe mental illness (e.g., Bipolar Spectrum Disorder, Schizophrenia Spectrum) residing in a long-term skilled nursing home facility. Qualitative and quantitative data, in the form of questionnaires, were collected and compiled after the completion of each group session. Data were collected after the first group session and subsequently for six total sessions. Results indicated increases in group comfort/cohesion (as defined as a desire to attend group sessions and willingness to share; Yalom, 2005), insight, emotional expression, enjoyment, and participation. It was also found that members preferred the large group size overall; however, this change in group size preference gradually increased based on the number of group sessions the member attended. Conclusions from this pilot study suggest the effectiveness of a novel application of the Tavistock method to large group work with a population of individuals with severe mental illness (Semmelhack, Ende & Hazell, 2013). Further research on large Tavistock style groups could focus on the use of the large group in the formation of a community setting in a long-term care institution and the dynamics of residing in a long-term facility. This study furthers research in group work, treatment approaches for individuals with severe mental illness, and treatments for individuals residing in a nursing home facility.